Kinetics and Mechanism of Oxidation of N-Methyldiethanolamine by Dihydroxydiperiodatonickelate(IV) in Alkaline Liquids - Shan, J.H.; Shen, H.X.; Wang, X.Q.; Wang, H.Y. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of N-methyldiethanolamine (MDEA) by diperiodatonickelate(IV) (DPN) in alkaline liquids at a constant ionic strength has been studied spectrophotometrically in the temperature range of 293.2–313.2 K. The reaction shows first order dependence on [DPN] and fractional order with respect to [MDEA]. The observed rate constant (kobs) decreased with increasing [IO4–] and increased with increasing [OH–]. The added salts did not affect the rate. A mechanism involving the diperiodatonickelate(IV) (DPN) as the reactive species of the oxidant has been proposed. The rate constants of the rate-determining step and the activation parameters were calculated.